Spatio-temporal change of ecosystem services as a key to understand natural resource utilization in Southern Chile - Locher Krause, Karla Estela; Lautenbach, Sven; Volk, Martin (Regional environmental change, 2017)
The understanding of how ecosystem services are distributed across the landscape and their change over time provides key information to manage multi-functional landscapes. To balance the conflicting demands on land multi-scale assessments are highly relevant, especially in biodiversity hot spot areas as the Valdivian temperate rain forest. We quantified six ecosystem services linked to forest...